PENGARUH PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BONE BOLANGO - Srihantuti Paramata; Hans Ngabito (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2022)
This study aims to determine how the effect of restaurant tax revenue on local revenue in Bone Bolango Regency. This study uses a quantitative approach, and the data sources used in the analysis use secondary data from the last five years (2016-2020). The analytical tool used to answer the established hypothesis is using simple regression analysis.The results showed that the restaurant tax had no significant effect on local revenue in Bone Bolango Regency. This effect is not significant because it is shown by the result of the determination value (Rsquare) where the value is equal to zero. This means that any increase in restaurant taxes does not have a significant effect on increasing local revenue in Bone Bolango Regency in the 2016-2020 period. The contribution of restaurant taxes to regional original income is quantitatively still relatively small compared to other sources of revenue such as regional levies, street lighting taxes and so on. Restaurant Tax is only able to provide an average contribution in 5 years (2016-2020) of only Rp. 1,039,000,000 while the average PAD revenue in the last five years is Rp. 73,032,748,896.48,- This means that the contribution of restaurant tax to local revenue is only 1.73 percent in the last five years.